Porous CuO catalysed green synthesis of some novel 3-alkylated indoles as potent antitubercular agents - Gulzar A. Khan; Javeed A. War; Gowhar A. Naikoo; Umar J. Pandit; Ratnesh Das (Journal of Saudi Chemical Society, 2018)
A green multicomponent one pot synthesis of novel 2-(1H-indol-3-ylmethyl)-5,5-dimethyl-cyclohexane-1,3-diones (4a–l) in excellent yields was conveniently carried out in aqueous medium at room temperature over mpCuO as heterogeneous catalyst. The synthesised 3-alkylated indoles were characterised by FTIR, 1H NMR, 13C NMR and HRLCMS. The nanocatalyst was facially synthesised via a green sol–gel route and characterised by SEM, TEM, EDX, PXRD, BET and FTIR. The porous nanocatalyst can be recycled five times without significant drop in product yield. Docking studies against enoyl acyl carrier protein reductase predicts that the compounds bind at the active site with high binding affinity values. The compound 4k (MIC, 15 μg/mL) shows comparable activity in reference to Isoniazid at the same concentrations against MT H37 Rv.